Development of a decellularized extracellular matrix-derived wet adhesive for sustained drug delivery and enhanced wound healing - Xinming Wang; Haonan Zhang; Weichang Xie; Bei Qian; Shixing Huang; Qiang Zhao; Xiaofeng Ye (Materials Today Bio)
Complete tissue recovery following traumatic injury remains a major clinical challenge. While tissue adhesives show promise for managing traumatic injuries, developing materials with robust wet adhesion and high biocompatibility remains difficult. Decellularized extracellular matrix (ECM)-derived materials are widely utilized in tissue engineering due to their superior biocompatibility and bioactivity. In this study, a wet adhesive is developed by functionalizing ECM with dopamine. The resulting ECM-dopamine exhibits strong wet adhesion and excellent biocompatibility. Furthermore, ECM-dopamine can be engineered into a drug delivery platform for small agents and macromolecules. Solid lipid nanoparticles (SLNs) are incorporated into ECM-dopamine to enable sustained release of small molecules. The ECM-dopamine-SLN system ensures sustained drug release for at least one week upon adhesion to target tissues. ECM-dopamine-SLN loaded with antimicrobials accelerates wound healing and promotes angiogenesis by modulating the inflammatory response in a mouse skin excision model. Additionally, ECM-dopamine can deliver bioactive macromolecules to injured tissue. ECM-dopamine loaded with insulin-like growth factor-1 promotes skeletal muscle regeneration in a mouse volumetric muscle loss model, likely through the modulation of M2-like macrophage polarization. The dual functionality of ECM-dopamine as both a wet adhesive and a drug delivery platform offers significant potential for regenerative medicine applications.